Characterization and Nitrate Reduction Activity of Bacteria Isolates from Groundwater in Yogyakarta as a Potential for In-Situ Bioremediation - Abigail Yemima; Endah Retnaningrum (Geological Engineering Department Universitas Gadjah Mada, 2025)
Groundwater pollution is common in densely populated areas due to the high discharge of domestic as well as agricultural waste. As a result, nitrate is one of the pollutants that is commonly found within the affected groundwater system. Yogyakarta is especially vulnerable to nitrate pollution due to the co-occurrence of rapid urban expansion and agricultural activities. High nitrate concentration in groundwater leads to many adverse effects on the environment, as well as human health. Therefore, this research was conducted to measure the capacity of indigenous aerobic nitrate-reducing bacteria found within the groundwater in Yogyakarta as a potential agent for in-situ bioremediation. A total of 19 indigenous bacteria were isolated from groundwater samples in Yogyakarta and were tested for their nitrate reduction activity. Two of the hight efficient isolates in reducing nitrate aerobically were then measured for their nitrate reduction activity every 24 hours within a 3-day incubation period. The phenotypes of the two bacteria isolates were characterized through the observation of cell morphology, colony morphology, and biochemical tests. Out of the two bacteria isolates, bacteria isolate 1 with similar characteristics to Pseudomonas sp was the most efficient in reducing nitrate, with 95.38% of total nitrate removed and a nitrate reduction activity of 40.67 mgL−1h.